Space debris as a threat to space sustainability - Kadir Yozkalach (The Central European Review of Economics and Management (CEREM), 2023)
Aim: The issue of space debris (or space junk) is an important aspect of the sustainability of space. If not properly managed, the accumulation of space debris could make some orbital paths too dangerous to use, potentially limiting our ability to explore and utilize space. This study aims to gain a better understanding of the space debris problem. Design / Research methods: This article is based on a review of official statistics, policy papers, and media coverage related to the topic of space debris. Findings: The data shows that intentional and non-intentional debris-creating events are still occurring. The increasing amount of debris brings higher risks to functional satellites and missions. While there are new projects to mitigate debris, these are challenging to put into action due to their high cost and high level of technology. Originality: This paper presents an overview of the space debris problem in the context of the sustainability of space, by focusing on legal and technological aspects. The paper also touches upon different ways to mitigate space debris.
Keywords: Q56; Q57; 330; Space debris; space sustainability; satellite; debris mitigation